Exploring the performance and mass-transfer characteristics of porous zinc anodes for membraneless hybrid-flow batteries - Tang, Lina; Dai, Shuyang; Leung, Puiki; Mohd Rusllim, Mohamed; Zeng, Yikai; Zhu, Xun; Flox, Cristina; Shah, Akeel A.; Liao, Qiang (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Zinc-based hybrid-flow batteries are considered as a promising alternative to conventional electrochemical energy-storage systems for medium- to large-scale applications due to their high energy densities, safety, and abundance. However, the performance of these batteries has been limited by issues such as dendritic growth and passivation of zinc anodes during charge–discharge cycling. To address this challenge, a variety of two- and three-dimensional zinc anodes have been investigated. While two-dimensional zinc anodes have been extensively studied, there has been limited investigation into three-dimensional zinc anodes for hybrid-flow batteries. This study highlights the potential of three-dimensional zinc anodes to mitigate overpotentials and improve the mass transport of active species to promote negative electrode reactions. The performance of a membraneless flow battery based on low-cost zinc and organic quinone was herein evaluated using experimental and numerical approaches. Specifically, the use of zinc fiber was shown to yield an average coulombic efficiency of approximately 90% and an average voltage efficiency of approximately 82% over the course of 100 cycles at a current density of 30 mA cm−2. These results indicate the viability of using zinc fiber anodes to improve the performance of existing hybrid-flow batteries.